STRENGTHENING OPERATIONAL PERFORMANCE THROUGH MANAGEMENT ACCOUNTING PRACTICES: EVIDENCE FROM A MODERN COFFEE SHOP - Mellisa Agustin Susanto; Dewanika Nega Riyana; Natasya Yudhiani Putri; Sisilia Margaretha (Jurnal Ilmiah Mahasiswa Akuntansi Universitas Tulungagung, 2024)
Micro, Small, and Medium Enterprises (MSMEs) require effective management accounting practices to improve operational efficiency and ensure business sustainability. However, many small businesses continue to rely on conventional accounting records and have not fully integrated management accounting functions into managerial decision-making. This study aims to examine the implementation of management accounting practices at Warkop Masa Kini by focusing on three managerial functions: control, cost calculation, and planning. A qualitative research approach was employed using primary data collected through unstructured interviews with the business owner, direct observations, and document analysis. The data were analyzed using an interactive analysis model consisting of data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that Warkop Masa Kini has implemented management accounting practices through standardized production control, systematic identification of raw material, labor, manufacturing overhead, and non-production costs, as well as strategic business planning supported by market research and social media marketing. Although these practices remain relatively simple and are primarily based on conventional financial records, they provide essential information for operational control, pricing decisions, cost management, and business planning. The study highlights the practical importance of integrating management accounting functions into the daily operations of MSMEs to improve managerial decision-making and operational performance. The findings also contribute to the management accounting literature by demonstrating how basic accounting practices can support business sustainability and competitiveness in small food and beverage enterprises.